2022
DOI: 10.1111/and.14406
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0076305 facilitates prostate cancer development via sponging miR‐411‐5p and regulating PGK1

Abstract: Prostate cancer (PCa) is a common malignant tumour, which ranks the second most frequent cancer (1.4 million new cases) and the fifth leading cause of cancer-related deaths (375,000 deaths) among men in 2020 (Sung et al., 2021). Although great progress has been achieved in therapeutic over the past few decades, the 5-year overall survival of PCa patients is still poor because of the metastasis and recurrence (Wu et al., 2017). Most PCa patients are diagnosed at late stages due to these patients with symptoms h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…CircRNA has a closed ring structure, is structurally stable and highly conserved, and is engaged in regulating cell proliferation and apoptosis. It has been suggested that circRNA makes a vital regulatory effect on the occurrence and development of PCa 3–5 . For instance, Li et al discovered that circ‐0044516 played a carcinogenic role in PCa and downregulated of it inhibited the proliferation and metastasis of PCa cells 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CircRNA has a closed ring structure, is structurally stable and highly conserved, and is engaged in regulating cell proliferation and apoptosis. It has been suggested that circRNA makes a vital regulatory effect on the occurrence and development of PCa 3–5 . For instance, Li et al discovered that circ‐0044516 played a carcinogenic role in PCa and downregulated of it inhibited the proliferation and metastasis of PCa cells 22 .…”
Section: Discussionmentioning
confidence: 99%
“…As an important part of the non‐coding RNA family, circRNA is implicated in the occurrence and progress of multiple diseases and can be applied as a biomarker or therapeutic target for novel and promising human tumors. Currently, it has been found that circ_0003258, circ_0076305, circCEMIP, circ_0004087 and other circRNAs are dysregulated in PCa and participate in the development of prostate cance 3–8 . By analyzing PCa circRNA chip (GSE155792), our research group found that circSSPO (circ_0082878) was abnormally high expressed in PCa tissues.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Existing research has established connections between circRNAs and various physiological and pathological processes. Some studies, such as those by Ding et al [ 29 ] and Gao et al [ 30 ], suggest that the dysregulation of certain circRNAs may influence PCa progression and drug sensitivity. However, the role of circRNAs in PCa still requires more comprehensive investigation.…”
Section: Discussionmentioning
confidence: 99%